Polymorphism at the apical membrane antigen 1 locus reflects the world population history of Plasmodium vivax - Grynberg, Priscila (BioMed Central, 2008)
BACKGROUND: In malaria parasites (genus Plasmodium), ama-1 is a highly polymorphic locus encoding the Apical Membrane Protein-1, and there is evidence that the polymorphism at this locus is selectively maintained. We tested the hypothesis that polymorphism at the ama-1 locus reflects population history in Plasmodium vivax, which is believed to have originated in Southeast Asia and is widely geographically distributed. In particular, we tested for a signature of the introduction of P. vivax into the New World at the time of the European conquest and African slave trade and subsequent population expansion. RESULTS: One hundred and five ama-1 sequences were generated and analyzed from samples from six different Brazilian states and compared with database sequences from the Old World. Old World populations of P. vivax showed substantial evidence of population substructure, with high sequence divergence among localities at both synonymous and nonsynonymous sites, while Brazilian isolates showed reduced diversity and little population substructure. CONCLUSION: These results show that genetic diversity in P. vivax AMA-1 reflects population history, with population substructure characterizing long-established Old World populations, whereas Brazilian populations show evidence of loss of diversity and recent population expansion. NOTE: Nucleotide sequence data reported is this paper are available in the GenBank™ database under the accession numbers EF031154 – EF031216 and EF057446 – EF057487